Tribology and Industry: From the Origins to 4.0 - Ciulli, Enrico (Frontiers in Mechanical Engineering, 2019)
There is an increasing diffusion of the industry 4.0 concept today. The fourth industrial revolution, following three other previous industrial revolutions, is considered related to the introduction of modern information and communication technologies in production. Tribological concepts are much older than industry. Tribology has always been connected to industrial problems from the birth of industry. It was strongly connected with the previous industrial revolutions and it is surely related to industry 4.0. In this work, the main aspects of the four industrial revolutions and the main evolutions of tribology are firstly reviewed from a historical point of view. The relationships between tribology and industry are described with particular attention to the aspects that relate the modern tribology 4.0 to industry 4.0. Tribology can have in particular a big impact on the industrial needs to reduce losses and wastes, for instance with the development of new tribological components and materials also in connection with electronic smart systems and taking advantage of the information and communication technologies.